A Survey on Bio-Inspired Algorithm for SQL Injection Attacks. - Jody, Zainab H. (Journal of Basrah Researches (Sciences), 2024)
SQL injection attacks cause significant threats to the security of online applications. It leverages vulnerabilities in database systems and can result in unauthorized access to and compromising sensitive data. This study investigates the use of bio-inspired algorithms to tackle such attacks, assessing their applications and potential for enhancing cybersecurity measures against SQL injection attacks. In this review, we describe the basic definition, causes, types, and prevention mechanisms of SQL injection attacks. In addition, we examine the use of various bio-inspired algorithms to solve the problem of SQL injection attacks. This study concludes the importance of continuously improving detection methods, particularly those adopting bio-inspired algorithms since they achieved promising results.